Teachers’ Perceptions of the Integration of Aboriginal Culture Into the High School Curriculum - Kanu, Yatta (Alberta Journal of Educational Research, 2005)
Recently activities surrounding the integration of Aboriginal cultural knowledge, content, and perspectives into the school curriculum have increased in an attempt to increase school success and retention among Aboriginal students. But how do public schoolteachers, mainly non-Aboriginal and belonging to Canadian mainstream culture, perceive this integration? An ethnographic study conducted among 10 teachers from three public high schools revealed that although there was an expressed openness to the integration of Aboriginal knowledge and perspectives into the school curriculum, in practice little or only moderate headway is being made. What teachers integrated, how they integrated it, and what they perceived as challenges to, and facilitators of, integration are discussed in this article. Based on the research findings, 10 recommendations are made to guide policy and practice in the integration of Aboriginal perspectives.